Implementasi Desain Pengembanagan Kurikulum Merdeka Pada Mapel PAI Di SMK Darunnajah Banjarmangu - Naufal Karunia Saputra; Abdul Majid; Chairani Astina (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this thesis is to: Explain how the Merdeka Curriculum is applied to the subjects of Islamic Religious Education and Character at Darunnajah Vocational School, Banjarmangu; and Provide an explanation of the design for the development of the Independent Curriculum in the subjects of Islamic Religious Education and Character at Darunnajah Vocational School, Banjarmangu.The author uses descriptive research with a qualitative approach and field research. To collect data, this research uses observations, in-depth interviews (in-depth interviews), and documentation. On the other hand, the author uses data reduction methods, data visualization, conclusions, or verification in data analysis techniques which are carried out with the aim of facilitating understanding of problem phenomena that occur and providing solutions to problems.The results of the research show that the implementation of the Independent Curriculum in Islamic Religious Education and Character Education Subjects at Darunnajah Banjarmangu Vocational School has been carried out well. This starts with PAI teachers preparing themselves to apply learning, namely creating learning tools and learning flows, from initial, core, and closing. Students then carry out the Project for Strengthening the Pancasila Student Profile (P5) outside the classroom. At Darunnajah Banjarmangu Vocational School, the design for developing the implementation of the Independent Curriculum in PAI subjects is to take part in workshops, increase teacher creativity, and share to change the way of teaching to make it better.